Directly deposited MoS2 thin film electrodes for high performance supercapacitors. Issue 47 (10th November 2015) - Choudhary, Nitin; Patel, Mumukshu; Ho, Yee-Hsien; Dahotre, Narendra B.; Lee, Wonki; Hwang, Jun Yeon; Choi, Wonbong
Abstract : We demonstrate the direct deposition of two-dimensional (2D) MoS2 thin film on Cu-foil and polymer substrates, exhibiting an excellent capacitance and outstanding cyclic stability. The MoS2 based supercapacitors will enable new opportunities in flexible electronics and energy devices. Abstract : Two dimensional (2D) layered materials have recently attracted significant research interest owing to their unique physical and chemical properties for efficient electrochemical energy storage devices. Here, we present a neoteric approach to fabricate high performance MoS2 thin film supercapacitor electrodes by using a direct magnetron sputtering technique. The novel three-dimensional (3D) porous structure of the MoS2 film exhibits an excellent capacitance of ∼330 F cm −3 along with a high volumetric power and energy density of 40–80 W cm −3 and 1.6–2.4 mW h cm −3, respectively. Moreover, the optimized MoS2 electrode shows an outstanding cyclic stability, yielding capacitance retention over 97% after 5000 cycles of charging/discharging. The contemporary approach to MoS2 supercapacitor electrode fabrication will enable new opportunities in flexible electronic and energy devices.